1996
DOI: 10.1002/(sici)1097-0215(19961104)68:3<384::aid-ijc18>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Anti-cancer agent OK432 induces manganese superoxide dismutase in human granulocytes

Abstract: Manganese superoxide dismutase (MnSOD) is a mitochondrial enzyme involved in scavenging O2-. OK432, a Streptococcal preparation, has anti-tumor activity and is also known to be a biological-response modifier. In this study, we have examined the regulation of MnSOD gene by OK432 in human granulocytes. Granulocytes had a low activity of MnSOD; OK432 increased MnSOD mRNA levels in a dose-dependent manner and its activity in granulocytes. OK432 also induced the MnSOD mRNA in HL60 promyelocytes, while not affecting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2000
2000
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
(2 reference statements)
1
2
1
Order By: Relevance
“…They did not measure immunoreactive protein or Mn SOD activity or effects of Mn SOD induction on the oxidant or drug resistance. The results of our and other recent studies (1,9,11) cannot rule out the possibility that Mn SOD activity may also be induced by cytotoxic drugs in vivo.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…They did not measure immunoreactive protein or Mn SOD activity or effects of Mn SOD induction on the oxidant or drug resistance. The results of our and other recent studies (1,9,11) cannot rule out the possibility that Mn SOD activity may also be induced by cytotoxic drugs in vivo.…”
Section: Discussioncontrasting
confidence: 91%
“…Few studies have investigated Mn SOD induction by cytotoxic drugs. Akashi et al (1) have shown that the anticancer drug OK-432 leads to elevation of Mn SOD in human granulocytes. Das and White (11) showed that anticancer drugs such as paclitaxel, vinca alkaloids (vinblastine and vincristine), and anthracyclines (daunomycin and doxorubicin) may cause activation of nuclear factor-B, and recently, Das et al (9) also reported that mRNA of Mn SOD was upregulated by cytotoxic drugs through a protein kinase-dependent mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…21 OK432 is reported to be effective in promoting the production of IL-1 and tumor necrosis factor (TNF)-α by neutrophils. 35 Accordingly, in this study, significant increases in intraperitoneal IL-, MIP-1α, and IL-6 corresponded with neutrophil accumulation. It appears that these cytokines and chemokines not only perform important functions in the intraperitoneal accumulation of lymphocytes and macrophages, 36 but also act on inflammatory cells and tumor cells to induce the expression of adhesion molecules such as ICAM-1 and CD11b/CD18, 37 leading to the acquisition of specific tumor immunity.…”
Section: Discussionsupporting
confidence: 59%
“…The basal expression of MnSOD is usually low, often hardly detectable, but the enzyme is induced by hyperoxia10, irradiation12, cytokines such as tumour necrosis factor13, interleukins14 and interferon15, and changes in the cellular redox state16. Recently, up‐regulation of MnSOD has also been shown to occur in response to the exposure to various cytotoxic drugs, at least in human lung adenocarcinoma cells and human granulocytes17, 18. Several, but not all, studies have also emphasized the importance of superoxide dismutase in the protection of cells and tissues against hyperoxia, cytokines and possibly cytotoxic drugs, both in vitro and in vivo 13, 19–23.…”
Section: Introductionmentioning
confidence: 99%